The Role of the Office of Religious Affairs in Addressing Underage Marriage - Putri, Nadia; Putri Utami, Melya; Rahmi, Zulhijatur; Putra, Dontes (Samara: Journal of Islamic Law and Family Studies, 2025)
Child marriage is a complex issue that remains prevalent in Indonesia, despite being regulated by Law No. 16 of 2019, which sets the minimum age for marriage at nineteen years. This phenomenon not only impacts children's fundamental rights, such as access to education and healthcare, but also has the potential to trigger long-term social, economic, and psychological issues. This study aims to analyze the extent to which the Religious Affairs Office fulfills its role in preventing child marriage, as well as to identify the challenges and strategies implemented within the social and cultural context of the local community. This study uses a qualitative approach with a field study method. Data was collected through in-depth interviews with Religious Affairs Office officials, religious leaders, village officials, and the community, and analyzed using descriptive qualitative methods. The results of the study show that the Religious Affairs Office has a strategic role in preventing child marriage, particularly through religious counseling and age verification of prospective brides and grooms. However, this role still faces significant obstacles, such as low public legal awareness, cultural and economic pressures, and the limited authority of the Religious Affairs Office to reject marriages that have obtained a dispensation from the court. However, the active involvement of the Office of Religious Affairs in collaborating with other agencies and community leaders has reduced the incidence of child marriage in recent years. The implications of this study emphasize the importance of strengthening the institutional capacity of the Office of Religious Affairs as the frontline in protecting children's rights.